Penerapan Metode Short Time Fourier Transform (STFT) dalam Menentukan Frekuensi Dasar Alat Musik Talempong Minangkabau - Hernanda, Fachri; Yusfi, Meqorry (Universitas Andalas, 2024)
At this research has determined the fundamental frequency of talempong musical instruments using the Short Time Fourier Transform (STFT) method. The research is divided into three stages, namely recording dataset retrieval, method implementation and base frequency analysis. In this research, sound recordings of talempong are collected into a dataset which is divided into several frequencies and then synthesized using the STFT methods then synthesized using the STFT method to determine the frequency of the talempong sound signal to determine the frequency of the talempong sound signal. The frequency value from the STFT process is then compared with the general base frequency to determine the percentage of accuracy of the talempong sound synthesis. From this research, the results obtained average error value of 4,39% and an accuracy percentage of 95,61%.